Variety of Spice Processing Equipment at The National Awakening Museum Spice Path Exhibition - Pradini, Gagih; Awaloedin, Dipa Teruna; Agustiani, Fitri; Suhino, Aushaf Hisham; Hanifa R, Ravanie; Prisillia, Putri Aisha (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
Spices are parts of plants that are used as spices, flavourings, flavourings and, to some extent, as food preservatives (FAO, 2005). Spices are aromatic plants or plant parts used in food with the main function of adding flavour. The use of spices in cooking is well-known (Duke et al, 2002). Spices are not only associated with food, but have also been used since time immemorial as herbal remedies, cosmetics, and antibacterial agents. So that several activities emerged that introduced and made an exhibition and festival about the richness of spices. One of the things is an event that takes the theme of the spice path or spice country which was originally organized by the Spice State Foundation. This implies how spices were symbolized as the past glory of the archipelago and are now revived as a means to imagine Indonesia. The research method involves two approaches, namely a literature study and a direct visit to the Spice Path Exhibition at the National Awakening Museum.